Elevated expression of cholesterol transporter LRP-1 is crucially implicated in the pathobiology of glioblastoma - N. R., Shruthi; Behera, Minakshi M.; Naik, Sanoj Kumar; Das, Sunil Kumar; Gopan, Sooraj; Ghosh, Amit; Sahu, Rabi Narayan; Patra, Susama; Purkait, Suvendu (Frontiers in Neurology, 2022)
Glioblastoma (GBM) is the most common primary malignant brain tumor with a grave prognosis. The present study evaluated the expression of Cholesterol transporter [importer -Lipoprotein Receptor-related Protein-1 (LRP-1) and exporter -ATP-binding cassette transporters-1 (ABCA-1)] in GBM and their implications in tumor-biology, clinical outcome and therapeutic potentials. The mRNA and protein expression was assessed by qRT-PCR and immunohistochemistry, respectively, in 85 GBMs. For comparison, 25 lower-grade astrocytomas (IDH-mutant, grade-2/3) [LGA] 16 cases of high-grade astrocytomas (IDH-mutant, grade-4) [HGA] were also evaluated. In-vitro analysis was performed on U87MG and LN229 glioma cell line. The expression of LRP-1 (mRNA and protein) was significantly higher in GBM than LGA, HGA and normal brain (NB) [p-values 0.007, 0.003 and <0.001 for mRNA; 0.024, <0.001 and <0.001 for immunohistochemistry]. Majority of the GBMs (82.4%) showed strong immunoreactivity for LRP-1, and all tumor cases were positive while the normal brain was negative. LRP-1 immunoreactivity positively correlated with the MIB-1 labeling index (p-value-0.013). LRP-1 knockdown in-vitro was associated with decreased cell survival, proliferation, migration, invasion, and increased apoptosis. Similar effect was also demonstrated by Receptor Associated Protein (RAP), a LRP-1 inhibitory drug. The silencing of LRP-1 was also associated with decreased cholesterol level. The ABCA-1 expression was higher in GBM than LGA and NB (p-value 0.011 and <0.001), however there was no significant association with other parameters. LRP-1 showed a positive correlation with ABCA-1 and associated with decreased expression with LRP-1 knock-down in-vitro. The expression of LRP-1 and ABCA-1 didn't correlate with overall survival in GBMs. Hence, LRP-1 is crucial for the tumor cells' survival and aggressive biological behavior which is maintain through the regulation of high intracellular cholesterol import. Its expression is significantly higher in GBMs and also implicated in the regulation of ABCA-1 expression. Considering its immune-positivity only in the neoplastic cell and strong positivity in GBM it may be a useful adjunct to the diagnosis. For the first time, the present study emphasized its role as a potential therapeutic target in the form of RAP which is presently being used in other neurological diseases under clinical trials.